A new skink (Scincidae: Liburnascincus) from rocky habitat on Cape York, northeast Australia - Hoskin, Conrad J.; Couper, Patrick J. (Zootaxa, 2015)
The genus Liburnascincus is composed of saxicoline skinks restricted to northeast Australia. This small radiation consists of one widespread species, L. mundivensis, found in a variety of rocky habitats in eastern Queensland, and two localized species, L. coensis and L. scirtetis, restricted to granite boulder habitats on Cape York Peninsula, in north Queensland. Here we describe a fourth species, L. artemis sp. nov., from the Bamboo Range, a low rocky range on Cape York. As for other Liburnascincus, the new species is a saxicoline skink that is active on boulder surfaces primarily early and late in the day. Liburnascincus artemis sp. nov. is most similar to L. mundivensis but can be diagnosed based on longer limbs, higher toe and finger lamellae counts, lower midbody scale count, and other aspects of morphology, scalation and colour pattern. Liburnascincus artemis sp. nov. is currently known from a very small area but further surveys will likely extend the range. It is geographically separated from L. mundivensis to the south by unsuitable habitat in the Laura region, but it may abut the range of L. coensis to the north. Despite a small distribution, L. artemis sp. nov. occurs at high density at the known sites and appears to be currently secure. In this paper we also discuss the distributions and biogeography of Liburnascincus more broadly.